Overall Complication Rates of DIEP Flap Breast Reconstructions in Germany-A Multi-Center Analysis Based on the DGPRaC Prospective National Online Registry for Microsurgical Breast Reconstructions - Heidekrueger, Paul I.; Moellhoff, Nicholas; Horch, Raymund E.; Lohmeyer, Joern A.; Marx, Mario; Heitmann, Christoph; Fansa, Hisham; Geenen, Matthias; Gabka, Christian J.; Handstein, Steffen; Prantl, Lukas; Von Fritschen, Uwe (Journal of Clinical Medicine, 2021)
While autologous breast reconstruction has gained momentum over recent years, there is limited data on the structure and quality of care of microsurgical breast reconstruction in Germany. Using the breast reconstruction database established by the German Society of Plastic, Reconstructive and Aesthetic Surgeons (DGPRaC), the presented study investigated the overall outcomes of deep inferior epigastric perforator (DIEP) flap reconstructions in Germany. Data of 3926 patients and 4577 DIEP flaps performed by 22 centers were included in this study. Demographics, patient characteristics, perioperative details and postoperative outcomes were accounted for. Centers performing < o 40 (low-volume (LV)) vs. >= o 40 (high-volume (HV)) annual DIEP flaps were analyzed separately. Overall, total and partial flap loss rates were as low as 2.0% and 1.1% respectively, and emergent vascular revision surgery was performed in 4.3% of cases. Revision surgery due to wound complications was conducted in 8.3% of all cases. Mean operative time and length of hospital stay was significantly shorter in the HV group (LV: 385.82 min vs. HV: 287.14 min; LV: 9.04 (18.87) days vs. HV: 8.21 (5.04) days; both p < 0.05). The outcome and complication rates deduced from the national registry underline the high standard of microsurgical breast reconstruction on a national level in Germany.
CRIS-Team WoS Importer:2021-03-26